Causes of Foreign Language Anxiety Among Students at Private Universities in Erbil - Mohammed Ismael, Dr. Shorsh (International Journal of Humanities and Education Development (IJHED), 2023)
Education is often regarded as an effective means of guiding students in the process of altering their behavior to conform to the standards of both themselves and the expectations of society. Both students' anxiety and their attitudes toward learning are seen as essential elements of the educational process; as a consequence, both factors play an important part in the development of second language skills. The primary objective of this study is to investigate the factors that cause students attending private institutions in Erbil to experience anxiety when they are studying a foreign language. A quantitative study approach was used to quantify the students' anxiety, and the factors that were taken into consideration were fear of receiving a negative evaluation, communication apprehension, and exam anxiety. The researcher was successful in collecting the necessary data after adapting and modifying a survey that had been established by previous academics. The researcher was successful in collecting 92 surveys that had all of the required fields filled out. Using multiple regression analysis, each of the study hypotheses could be evaluated. The findings of this research showed that a student's fear of experiencing negative anxiety was related to a greater level of anxiety when it came to the process of learning a new language, but a student's fear of performing poorly on a test was related to a lower value, among other factors.